Effect of chromosome 9 polymorphism on In Vitro Fertilization (IVF) treatment outcomes - Hayat, Muhammad Azhar; Yasmin, Munazza; Haider, Amra; Fatima, Kaneez; Wu, Menglan; Jing, Liu (Biological and Clinical Sciences Research Journal, 2025)
Chromosomal variants such as heterochromatic polymorphisms on the long arm of chromosome 9 (9qh+) and pericentric inversions [inv(9)] are not uncommon. Although some studies suggest an increased risk of miscarriage, most carriers appear phenotypically normal, and these variants are generally regarded as benign chromosomal polymorphisms. However, their potential impact on preimplantation embryo development and in vitro fertilization–embryo transfer (IVF-ET) outcomes remains uncertain. Objective: To evaluate whether 9qh+ and inv(9) affect preimplantation embryo development and clinical outcomes of IVF-ET, and to determine whether effects differ between male and female carriers. Methods: This retrospective study included 1,435 couples who underwent IVF-ET at the First Affiliated Hospital of Hainan Medical College between January 2015 and June 2020. Chromosome G-banding was performed before IVF-ET. The inv(9) group comprised 150 couples carrying pericentric inversions, with 821 couples of normal karyotype serving as controls (ratio 1:5.47). The 9qh+ group included 82 couples with at least one carrier, with 382 couples of normal karyotype as controls. IVF-ET outcomes—including number of oocytes retrieved, fertilization rates, cleavage rate, good-quality embryo rate, embryo transfer number, pregnancy rate, implantation rate, miscarriage rate, and live birth rate—were compared between groups. Subgroup analyses were conducted to assess differences between male and female carriers of the inv(9) chromosome. Statistical significance was set at P<0.05. Results: No significant differences were observed between inv(9) carriers and controls, or between 9qh+ carriers and controls, in oocyte yield, fertilization rates, embryo quality, cleavage rate, pregnancy rate, implantation rate, miscarriage rate, or live birth rate (all P>0.05). However, the live birth rate was significantly lower in female inv(9) carriers compared with male carriers and controls (23% vs. 41% vs. 36%, P = 0.03). Subgroup analysis showed statistically significant differences in infertility duration (4.8 vs. 5.9 vs. 10.6 vs. 5.6 years, P=0.01) and number of embryo transfers (1.47 vs. 1.79 vs. 2.0 vs. 1.6, P=0.001) when comparing inv(9)(p12;q13), inv(9)(p11;q13), and other inv(9) subgroups with controls. No significant differences were observed between 9qh+ carriers and controls. Conclusion: Pericentric inversion inv(9)(p12;q13) and male inv(9)(p11;q13) heterozygosity do not affect preimplantation embryo development or IVF-ET outcomes. Female carriers of inv(9)(p11;q13) exhibit normal embryo development but experience reduced live birth rates, indicating a sex-specific impact on clinical outcomes. Carriage of 9qh+ variants does not adversely influence embryo development or IVF-ET success.